2004
DOI: 10.21273/horttech.14.4.0628
|View full text |Cite
|
Sign up to set email alerts
|

Total Quercetin Content in Onion: Survey of Cultivars Grown at Various Locations

Abstract: Because of potential benefits on human health, the content of quercetin, the major flavonol found in onion (Allium cepa), could become a selection trait in breeding programs. Total flavonol concentration in onion was examined by spectrophotometric analysis at 374 nm in three long-day hybrid cultivars grown at three locations (Parma, Idaho; Grand Rapids, Mich; Elba, N.Y.), and in three shortday hybrid cultivars grown at one location in Georgia in three different fields. Mean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In the present study, mean total flavonol content varied between 430 and 753 mg • kg -1 on a FW basis (Table 4). This level is comparable to previously reported results of yellow onions, ranging between 158 and 1187 mg • kg -1 on a FW basis (Lombard et al, 2004;Mogren et al, 2006;Slimestad et al, 2007), but it is considerably lower than total flavonol content of red onions (Pérez-Gregorio et al, 2010). Mean total polyphenol content varied between 607 and 1029 mg • kg -1 on a FW basis (Table 4).…”
Section: Resultssupporting
confidence: 89%
“…In the present study, mean total flavonol content varied between 430 and 753 mg • kg -1 on a FW basis (Table 4). This level is comparable to previously reported results of yellow onions, ranging between 158 and 1187 mg • kg -1 on a FW basis (Lombard et al, 2004;Mogren et al, 2006;Slimestad et al, 2007), but it is considerably lower than total flavonol content of red onions (Pérez-Gregorio et al, 2010). Mean total polyphenol content varied between 607 and 1029 mg • kg -1 on a FW basis (Table 4).…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, several recent studies have shown that different types of natural polyphenols may have neuroprotective effects both in vitro and in vivo, 6-10 partly due to their electron scavenging properties. 14 Several research projects have undertaken the isolation and identification of quercetin and its glycosides in various fruits and vegetables, including onion, 15 kale, 16 broccoli, 17 apple skin, 18 green tea, 19 and grapes and wine. 8,[11][12][13] Quercetin is a polyphenolic compound that occurs in vegetables and fruits mainly as different glycosides, although the skin of the fruit/vegetable commonly contains higher amounts of the quercetin aglycone.…”
Section: Introductionmentioning
confidence: 99%
“…The long-day cultivars from Northern Europe and their close relatives contain higher concentrations of quercetin glucosides than those of Japanese and North American. In long-day cultivars, total quercetin content was higher than in short-day cultivars being independent of the growing origin [51,52].…”
Section: Quantitative Data Compilation Presented Inmentioning
confidence: 85%